Determination of Molar Solubility and Swelling Degree mole of the Polyster Polyols in Water, Saline, Cu(II) and Urea Solution as Swelling Agents - NARKHEDE, B.N.; INGALE, R.B.; RATHOD, S.D.; RANE, P.H. (Asian Journal of Chemistry, 2010)
Previous works on poly(vinyl alcohol) (PVA) has effect on its swelling. Its hydroxyl groups have been studied as swollen elastic networks and as water sorbents. Various polymers have been prepared from PVA and different acids such as anthranilic acid, amino acetic acid and p-amino benzoic acid and studied for their solubility and swelling properties to correlate them with various structural factors. These polysterpolyols have been studied for solubility and swelling in water, saline, Cu(II) and urea solutions for the purpose of comparing solubility with structural characteristics. Molar solubility decreases with increase in hydroxyl groups. The swelling degree mole (g/g) is calculated, It was observed that, these values are increasing with increase in hydroxyl groups.